The U.S. Tomato Industry: An Overview of Production and Trade - Zhengfei Guan; Trina Biswas; Feng Wu (EDIS)
Tomatoes are one of the world's most consumed vegetable crops. In the United States, domestic production meets about 40% of the total domestic demand for fresh-market tomatoes, with the rest of the demand met by imports, mostly from Mexico and Canada. Since 2000, however, fresh tomato production in the United States has exhibited a steady declining trend. One major reason is the increased competition from Mexico. This 4-page fact sheet written by Zhengfei guan, Trina Biswas, and Feng Wu and published by the UF/IFAS Food and Resource Economics Department argues for US government measures to help the domestic tomato industry resolve labor shortages and encourage research and development of labor-saving technologies such as mechanical harvesting to make the US tomato industry more competitive and sustainable. http://edis.ifas.ufl.edu/fe1027